2014
DOI: 10.3389/fendo.2014.00063
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis and Cryptorchidism

Abstract: Cryptorchidism represents the most common endocrine disease in boys, with infertility more frequently observed in bilateral forms. It is also known that undescended testes, if untreated, lead to an increased risk of testicular tumors, usually seminomas, arising from mutant germ cells. In normal testes, germ cell development is an active process starting in the first months of life when the neonatal gonocytes transform into adult dark (AD) spermatogonia. These cells are now thought to be the stem cells useful t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 41 publications
0
52
0
6
Order By: Relevance
“…U ndescended testis is one of the most common congenital abnormalities in male children, with an incidence rate of 1%. 1,2 The universally accepted and recommended treatment is orchiopexy. In the past decades, open inguinal orchiopexy has been the routine procedure for palpable undescended testis, and laparoscopic orchiopexy for nonpalpable testis.…”
Section: Introductionmentioning
confidence: 99%
“…U ndescended testis is one of the most common congenital abnormalities in male children, with an incidence rate of 1%. 1,2 The universally accepted and recommended treatment is orchiopexy. In the past decades, open inguinal orchiopexy has been the routine procedure for palpable undescended testis, and laparoscopic orchiopexy for nonpalpable testis.…”
Section: Introductionmentioning
confidence: 99%
“…Deleterious effects of cryptorchidism have been demonstrated in all cell stages of spermatogenesis (Goel et al, 2015). Previous studies reported retention of gonocytes and defective transformation of dark spermatogonia to primary spermatocyte, defective onset of meiosis (Hadziselimovic et al, 2007;Cobellis et al, 2014), germ cell degeneration in both retained and scrotal testes (Liu, 2012), congenital spermatogenic arrest (Sengupta, 2012) and reduction in fertility of the contralateral descended testis (Chung, 2011;Goel et al, 2015). However, other authors postulated that the contralateral scrotal testes are normal providing normal number of germ cells, normal distribution of dark and pale spermatogonia and primary spermatocytes (Hadziselimovic, 2008;Okpe & Ezeasor, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] It has been associated with infertility, increased risk of malignancy, testicular torsion, traumatic injury against adjacent structures, associated inguinal hernia, and psychological stigma of an empty scrotum. UDT can be categorized as congenital or acquired, and it can be defined in different ways, depending of the position of the testes: Canalicular, prepubic, prescrotal, superficial to the inguinal pouch, ectopic, and abdominal.…”
Section: Introductionmentioning
confidence: 99%
“…UDT can be categorized as congenital or acquired, and it can be defined in different ways, depending of the position of the testes: Canalicular, prepubic, prescrotal, superficial to the inguinal pouch, ectopic, and abdominal. 8,9 Besides all these possibilities, the UDT can be palpable (80%) and nonpalpable (20%). 8,10,11 At present, the gold standard for managing palpable UDT is open orchiopexy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation